2014
DOI: 10.5116/ijme.5412.e641
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of changes in cognitive and emotional empathy among medical students in the Caribbean

Abstract: Objectives:This study explored the empathy profile of students across five years of medical training. In addition the study examined whether the Jefferson Scale for Physician Empathy correlated with a measure of cognitive empathy, the Reading the Mind in the Eyes Test and a measure of affective empathy, the Toronto Empathy Questionnaire.Methods:The study was a comparative cross-sectional design at one Caribbean medical school. Students were contacted in class, participation was voluntary and empathy was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
77
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 34 publications
16
77
3
6
Order By: Relevance
“…In the other one, a study on Korean graduate students (Han 2016), the researchers claimed that according to the confirmatory factor analysis there lacked a goodness of fit in the single factor model, while according to the exploratory factor analysis the single factor was suggested. In our study, the internal consistency reliability of the TEQ was satisfactory at α = 0.72, comparable to the one reported by the manufacturers (Spreng et al 2009) and by other researchers (Baldner and McGinley 2014;Robinson and Wright 2013;Celik et al 2013;Totan et al 2012;Baltes , and Miu 2014;Youssef et al 2014). Taking into account that TEQ is scored on a scale from 0 to 4, the mean score 3.2 (SD = 0.4) found in our study suggests that our sample reported rather high levels of empathy or, in any case, higher than the mean score reported in the original questionnaire (Spreng et al 2009).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the other one, a study on Korean graduate students (Han 2016), the researchers claimed that according to the confirmatory factor analysis there lacked a goodness of fit in the single factor model, while according to the exploratory factor analysis the single factor was suggested. In our study, the internal consistency reliability of the TEQ was satisfactory at α = 0.72, comparable to the one reported by the manufacturers (Spreng et al 2009) and by other researchers (Baldner and McGinley 2014;Robinson and Wright 2013;Celik et al 2013;Totan et al 2012;Baltes , and Miu 2014;Youssef et al 2014). Taking into account that TEQ is scored on a scale from 0 to 4, the mean score 3.2 (SD = 0.4) found in our study suggests that our sample reported rather high levels of empathy or, in any case, higher than the mean score reported in the original questionnaire (Spreng et al 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, women scored higher in the TEQ, supporting similar findings that females tend to exhibit higher empathy than males (Spreng et al 2009;Totan et al 2012;Baltes , and Miu 2014;Youssef et al 2014;Toussaint and Webb 2005;Turnage et al 2012). These sex differences do not emerge in all empathy studies however, prompting Baldner and McGinley (Baldner and McGinley 2014) to state that self-report measures of empathy do not vastly differentiate among genders.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Most of the previous studies revealed similar results (Hojat et al 2002a;Hojat et al 2002b;Hojat et al 2002c;Hojat et al 2005;Kliszcz et al 2006;Kataoka et al 2009;Quince at al. 2011;Tavakol et al 2011;Chen et al 2012;Hasan et al 2013;Wen et al 2013;Leombruni et al 2014;Youssef et al 2014;Hojat & Gonnella 2015). On the other hand some studies did not find any difference among empathy levels of male and female students (Rahimi-Madiseh et al 2010;Roh et al 2010;Tavakol et al 2011;Williams et al 2015).…”
Section: Discussionmentioning
confidence: 99%